Stigma and the in(visible) perspectives and expectations of home oxygen therapy among people with chronic breathlessness syndrome: A qualitative study. (January 2019) - Breaden, Katrina; Collier, Aileen; Litster, Caroline; Allcroft, Peter; Currow, David C; Phillips, Jane L
Background: Chronic breathlessness syndrome in the context of advancing disease is distressing for all concerned. Oxygen is commonly prescribed in this setting; however, little is known about the perspectives of breathless people who either are on oxygen or are yet to have it prescribed. Aim: To understand and describe the perspectives and experiences of breathless people towards oxygen use at home. Design: This qualitative study utilised an interpretive description approach using semi-structured interviews and thematic analysis. Setting/participants: A total of 19 people with chronic breathlessness syndrome living in South Australia participated in semi-structured interviews. Participants were divided into sub-groups according to whether they were chronically breathless and (1) not using home oxygen ( n = 6), (2) using funded home oxygen for severe hypoxaemia ( n = 7) and (3) using home oxygen for palliation outside of funding guidelines ( n = 6). Results: Three main themes were identified: (1) managing distress and living with chronic breathlessness syndrome, with or without oxygen, requires a range of self-management strategies; (2) expectations of oxygen use: 'Not as good as I thought it would be'; and (3) the stigma of using oxygen: the visible and invisible. Conclusion: People living with chronic breathlessness struggle daily with both the progression of the underlying disease and the distressing nature of the syndrome. While oxygen does provide benefit for some people, its use and the perceptions of its use are often associated with both the visible and invisible manifestations of stigma. Clinicians need to promote self-management strategies and give careful thought to the prescribing of home oxygen, especially outside the current funding guidelines.